Metode Pendampingan Membaca Permulaan Siswa Fase A Kelas 1 di MI Muhammadiyah Klaseman Gatak Sukoharjo Tahun Ajaran 2025/2026 - Oktavani Putri Pratiwi; Suprapti (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to describe the methods used by teachers in supporting the early reading skills of Year 1 pupils at MI Muhammadiyah Klaseman, to identify the factors that support and hinder their implementation, and to explain the efforts made by teachers to overcome the obstacles that arise. This study employs a descriptive qualitative approach and was conducted at MI Muhammadiyah Klaseman Gatak, Sukoharjo, during the 2025/2026 academic year. The research subjects were Year 1 teachers, with the headteacher and pupils serving as supporting informants. Data were collected through observation, in-depth interviews, and documentation. Data validity was tested using source and method triangulation, whilst data analysis was carried out using the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate that teachers apply the phonetic method, the Structural Analytic Synthetic (SAS) method, and educational games in an integrated manner. Supporting factors include teacher consistency, the use of varied learning media, and institutional support. Hindering factors include differences in pupils’ initial abilities, time constraints, and a lack of support at home. Teachers overcame these obstacles through individual guidance, grouping based on ability, gradual repetition of material, and active communication with parents. This adaptive approach had a positive impact on the development of pupils’ early reading skills.